Peradaban Ekonomi Islam Masa Keemasan Dinasti Abbasiyah Dan Relevansinya Terhadap Ekonomi Kontemporer - Salimudin, Mumud; Khosyi’ah, Siah (Jurnal Ilmiah Wahana Pendidikan, 2025)
This article analyzes the Islamic economic trade that emerged during the Abbasid Dynasty, a period marked by progress and prosperity in the Islamic world. This article uses a qualitative methodology, specifically using a literature review approach. The results showed that economic civilization during the golden age of the Abbasid Dynasty was distinguished by two main principles, namely, economic thought and economic institutions. At this time, several economic thoughts emerged and developed both on microeconomic and macroeconomic scales. Abu Yusuf's economic thinking on macroeconomics can be observed in his Kitab al-Kharaj, while al-Shaibani examines microeconomics in his work al-Kasb. Yahya ibn Umar examined the principles of economics in his book Ahkam as-Suq, while Abu Ubayd addressed this issue in his Kitab al-Amwal. In addition to thinking about various economic fields, several economic institutions emerged and developed, including government finance, taxation, agricultural economic activities, trade, and industry. The Abbasid dynasty experienced rapid progress due to conducive political situations and conditions and state policies in advancing science and technology.